Virus diversity and an outbreak of group C rotavirus among infants and children with diarrhea in Maizuru City, Japan during 2002-2003 - Phan T.G. (2014)
A total of 236 fecal specimens collected from infants and children with gastroenteritis in Maizuru city, Japan from July 2002 to June 2003, were tested for the presence of rotaviruses, noroviruses, sapoviruses, astroviruses, and adenoviruses by RT-PCR, PAGE, RPHA, and latex agglutination methods. Among diarrheal viruses detected, group A rotavirus was the most prevalent (32.2%; 76 of 236) followed by norovirus GII (21.2%; 50 of 236), group C rotavirus (10.2%; 24 of 236), adenovirus (3.8%; 9 of 236), sapovirus (2.5%; 6 of 236), astrovirus (1.3%; 3 of 236), and norovirus GI (0.8%; 2 of 236), respectively. It is noteworthy that group C rotavirus infection was apparently confined only within the period of 5 months (December 2002 through April 2003). This pattern of infection implied that the outbreak of group C rotavirus in these patients, which was the first outbreak of gastroenteritis attributed to group C rotavirus in Maizuru city. Moreover, about half (12 of 24) of group C rotavirus infected cases were confined to infants and young children less than 3 years old. Another interesting feature of the study was the demonstration of the mixed infections with group C rotavirus and group A rotavirus, as well as group C rotavirus and norovirus GII in 20.8% (5 of 24) and 8.3% (2 of 24), respectively. This is the first report of gastroenteritis associated with the mixed infections with group C rotavirus and other viral enteropathogens such as norovirus. The results indicate that group C rotavirus could infect not only older children and adults but also infants and young children under 3 years old. © 2004 Wiley-Liss, Inc.